2002
DOI: 10.1021/ja012293h
|View full text |Cite
|
Sign up to set email alerts
|

Antihydrophobic Cosolvent Effects for Alkylation Reactions in Water Solution, Particularly Oxygen versus Carbon Alkylations of Phenoxide Ions

Abstract: Antihydrophobic cosolvents such as ethanol increase the solubility of hydrophobic molecules in water, and they also affect the rates of reactions involving hydrophobic surfaces. In simple reactions of hydrocarbons, such as the Diels-Alder dimerization of 1,3-cyclopentadiene, the rate and solubility data directly reflect the geometry of the transition state, in which some hydrophobic surface becomes hidden. In reactions involving polar groups, such as alkylations of phenoxide ions or S(N)1 ionizations of alkyl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
52
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 39 publications
2
52
0
1
Order By: Relevance
“…Propofol and analogs were purchased from Sigma-Aldrich or Acros (Geel, Belgium); compounds 2, 3, and 5 were synthesized as previously described (21,22). Ligand structures are given in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Propofol and analogs were purchased from Sigma-Aldrich or Acros (Geel, Belgium); compounds 2, 3, and 5 were synthesized as previously described (21,22). Ligand structures are given in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…As part of this, we also showed that we could determine the detailed transition state geometries of a number of important chemical reactions, a goal of chemistry that was hitherto completely impossible, by using such denaturants in water solution (22). The magnitude of the denaturant effect on reaction rates proved to be directly related to the amount of exposed hydrocarbon surface in the transition states for the reactions relative to that in the starting materials.…”
mentioning
confidence: 87%
“…In addition to steric effects that will contribute to the relative positioning of reactive and catalytic groups, it is conceivable that other chemical factors of selectivity in competing O and C alkylations of phenoxide ions might thus have become optimized in each enzyme. Solvent dielectric and polarity, S N 1 or S N 2 character of the transition state, and hydrogen bonding have been discussed in literature as factors affecting the position of alkylations of phenoxide ions [38]. Moreover, the hard-soft character of the phenoxide is considered important in determining the selectivity of oxygen vs. carbon alkylation [39].…”
Section: Mechanistic Implications For C-gtmentioning
confidence: 99%